Efeito da quercetina sobre a hiperglicemia induzida pelo tamoxifeno em ratas ovariectomizadas - Silva, Fernanda Coleraus (2015)
Tamoxifen was discovered in 1970 and classified as selective estrogen receptor modulator (SERM) being used as therapy in the treatment of breast cancer. Although benefits has been proven, side effects are intense, and are related to different mechanisms of toxic action, such as oxidative stress and changes in the glycolytic pathway that induce a hyperglycemia and liver damage. The administration of quercetin, a flavonoid with antioxidant potential, that has inhibitory effect on enzyme butyrylcholinesterase, an enzyme possibly associated with hepatotoxicity and hyperglycemia, has benefits on the adverse effects caused by tamoxifen. Thus, first to determine the effect of quercetin on the hyperglycemia caused by tamoxifen, ovariectomized rats were treated orally, with tamoxifen and quercetin; concluding that effects of quercetin are dependent on ratio quercetin/tamoxifen coadministered and the 4.5 ratio is more effective. After, trying to elucidate the mechanisms involved in changes in the glycolytic pathway, oxidative stress and liver damage perfusion was performed in rat liver, studying especially glycogenolysis and gluconeogenesis, using as an indicator of liver damage of butyrylcholinesterase activity and monitoring the oxidative stress. The results showed that quercetin has inhibitory effect on glucose production and enhances the effects generated by tamoxifen in gluconeogenesis, concluding that although quercetin is known for antioxidant activity, in certain concentrations (400 μM) intensifies the damage initially caused by tamoxifen, this effect doesn't occur with lower concentrations of quercetin (200 μM). Therefore, although quercetin has shown to be effective in reducing hyperglycemia caused by tamoxifen, the interaction of quercetin with tamoxifen should be viewed with caution since the effect of this interaction in carbohydrate metabolism is intense, can alter the intracellular redox environment, compromising its integrity and causing serious damage to liver tissue.